The moderating influence of language barrier on the relationship between safety management practices and safety behaviour among foreign workers at construction sites in Malaysia - Mukilan, Chelliah (2022)
Drawing upon the Goal Setting Theory and the Social Exchange Theory, this study examined the role of language barrier in moderating the effects of safety management practice (management commitment, safety training, employee involvement, safety communication and feedback, safety rules and procedures, and safety promotion policies) on self-reported foreign construction men’s safety behaviour (safety compliance and participation). Using a quantitative approach and cross-sectional survey, a total of 201 foreign workmen in Malaysia participated in the study. The Partial Least Square in Structural Equation Modelling (PLSSEM) and Statistical Software in Social Sciences (SPSS) were used to analyse the data. The findings supported the hypothesized direct ef fects of management commitment to safety (compliance and participation), safety training and safety participation workers involvement and behaviour (compliance and participation). In addition, the findings supported the hypothesized direct effects safety promotion policies on safety communication and feedback and safety behaviour (compliance and participation), safety rules and procedure and safety behaviour (compliance and participation), safety promotion and policies and safety compliance and language barrier and safety participation. Furthermore, language barrier moderated the relationship between management commitment and safety compliance, and the relationship between safety training, and safety participation. In order to achieve an optimally safe construction environment in the future, the management should focus on the implementation of safety management practices and consider construction workers language barrier when making decisions on how to improve safety. Finally, the theoretical and practical implications are discussed.